Single-Visit Endodontic Therapy and Root Canal Identification Practices among Croatian Dentists: Insights from a National Survey - Josipa Sović; Sanja Šegović; Ivona Bago; Jurica Matijević; Ivan Tomašić (Acta Stomatologica Croatica)
Objective: to analyze a single-visit endodontic treatment together with root canal detection practices in Croatia and investigate their relationship with reported postoperative pain, medication prescription, magnifying devices, rubber dam, radiographical checks before the procedure, cone-beam computed tomography (CBCT) and engine-driven instrumentation. Materials and Methods: A structured questionnaire was distributed via email to all Croatian dental practitioners, with 819 responses analyzed corresponding to an estimated 27% response rate. Statistical analyses included descriptive analysis and regression modelling. Results: Among Croatian practitioners, 27.9% frequently performed single-visit endodontic treatments. Male practitioners, practitioners with continuing education and ample experience, endodontic specialists, and those working in polyclinics or academic settings were more likely to adopt this approach. It correlated positively also with the use of advanced diagnostic and treatment tools (e.g., magnification devices, rubber dam, CBCT) and a reduction in antibiotic prescription. However, it was associated with increased reported analgesic prescription and a larger number of reported vertical tooth fractures. Practitioners reported less frequently using single-visit endodontic treatments for multi-rooted teeth and those with associated sinus tracts or periradicular lesions. Furthermore, practitioners more often performing single-visit endodontic treatment rate themselves better in finding additional canals, which is positively influenced by usage of radiography and magnification devices. In addition, continuing education has a positive effect on the root-finding abilities, but it decreases with years of their clinical experience. Conclusions: Single-visit endodontic treatment practice in Croatia is influenced by practitioner education, experience, and access to advanced equipment. While it offers benefits such as reduced antibiotic prescription, clinical attention and further research is needed to address potentially associated complications such as vertical tooth fractures and reliance on analgesics. Root finding abilities are positively influenced by continuing education. These findings underscore the role of education and resources in optimizing endodontic outcomes.